Is Earnings Uncertainty Relevant for Educational Choice? An Empirical Analysis for China - Joop Hartog; Xiaohao Ding; Juan Liao (Tinbergen Institute, 2011)
We use the method of Dominitz and Manski (1996) to solicit anticipated wagedistributions for continuing to a Master degree or going to work after completing theBachelor degree. The means of the distributions have an effect on intention to continue aspredicted by theory. The dispersions in these individual distributions have no effect onintention to continue, suggesting that anticipated earnings risk does not play a role in thedecision.
Keywords: D8; I21; J24; 330; wage expectations; educational choice; Bildungsertrag; Entscheidung bei Unsicherheit; Bildungsverhalten; Studierende; Beijing; China